Delving into the Secular Stagnation Hypothesis: A Firm-Level Analysis of the Private Sector's Excess Savings in Advanced Economies - Perez Artica, Rodrigo; Brufman, Leandro; Martinez, Lisana Belén (Comparative Economic Studies)
We document a persistent increase in excess savings (defined as the difference between gross savings and capital formation) and a steady decline of gross capital formation in a sample of non-financial firms from developed countries. These patterns developed even before the financial breakdown of 2007 reinforcing the case for a secular stagnation hypothesis. They go along with a deleveraging process and a decrease in the share of operating assets in total assets. We discuss three possible explanations for this long-term behavior: financial constraints, operative volatility, and the weakening of business dynamism itself. Fil: Perez Artica, Rodrigo. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Bahía Blanca. Instituto de Investigaciones Económicas y Sociales del Sur. Universidad Nacional del Sur. Departamento de Economía. Instituto de Investigaciones Económicas y Sociales del Sur; Argentina Fil: Brufman, Leandro. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Bahía Blanca. Instituto de Investigaciones Económicas y Sociales del Sur. Universidad Nacional del Sur. Departamento de Economía. Instituto de Investigaciones Económicas y Sociales del Sur; Argentina Fil: Martinez, Lisana Belén. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Bahía Blanca. Instituto de Investigaciones Económicas y Sociales del Sur. Universidad Nacional del Sur. Departamento de Economía. Instituto de Investigaciones Económicas y Sociales del Sur; Argentina